Business micro- environment Challenges of Supply chain network integration: case study Jordan Industrial Estate Corporation - M.AIgaribeh, Assist .prof. Dr Khaled (IJRDO - Journal of Applied Management Science, 2017)
The purpose this of the study was to identify the challenges which Supply Chain network integration face in its implementation on both domestic and international firms, Classifying these Challenges depending on their effect, And finding relation between these classes in Jordan Industrial Estate Corporation. The Questionnaires were sent to 140 employees working in the company. Only (124) were returned. The overall response rate for this study was 92%. This is regarded as relatively high, since the respondents are managers and they were supposed to be too busy to answer Questionnaire, Stratified random sampling was used for the research method: Beta , R , T-value .